Notary's Responsibility for the Criminal Act of Forgery of Authentic Deeds (Study of Decision Number 1003 K/Pid/2015) - Nuraini, Rubit Wahyu; Arifullah, Achmad (TABELLIUS: Journal of Law, 2025)
Notary is a public official who is authorized to make authentic deeds and other authorities as referred to in Law Number 2 of 2014 concerning the amendment to Law Number 30 of 2004 concerning the Position of Notary. This study aims to analyze the responsibility of notaries for the criminal act of forgery of authentic deeds with a case study in Decision Number 1003 K/Pid/2015. The main focus of this study is to understand the legal position of notaries in the context of making authentic deeds and the legal implications that arise if forgery occurs. In addition, this study also explores aspects of criminal and civil law related to the responsibility of notaries in carrying out their duties, in order to provide recommendations for legal protection for the injured parties. The research method used is a normative legal approach by examining laws and regulations and case approaches, legal doctrines, and case studies of court decisions. Data were collected through literature studies and analysis of related legal documents. The analysis was carried out descriptively qualitatively to obtain a comprehensive picture of the notary's responsibility in cases of forgery of authentic deeds. The results of the study indicate that notaries have legal responsibilities both civilly, criminally, and administratively in making authentic deeds. Decision Number 1003 K/Pid/2015 reveals that forgery of authentic deeds can result in criminal sanctions for notaries who are proven to be negligent or intentionally violating the law. From this study, it is recommended that there be strengthening of regulations and supervision of the notary profession in order to prevent abuse of authority in making authentic deeds.